Les structures économiques de la Belgique et leur spatialité, des Golden Sixties à aujourd’hui - Christian Vandermotten (Belgeo)
This empirical paper deals with the structural and geographical evolution of the Belgian economic pattern from the Fifties, in a macrogeographical perspective, from the national to the municipal scale. It uses systematically added value as indicator. Before 1975, the structural evolutions were mainly registered inside the industrial sector. The Fordist developments, the coal-mines crisis and the obsolescence of a part of the old heavy manufacturing led to a shift of the economy from the South to the North of the country. During the ‘80 and ‘90 decades, the transformation of the industrial to a post-industrial economy was accompanied by a process of metropolitanisation. The structures and their geographical pattern remained more stable since the beginning of the present Century, even if the two Walloon main urban areas always suffer from their economic and social legacies. The best economic outcomes are now observed in the large periphery of Brussels metropolitan area.